2012
DOI: 10.1063/1.3690470
|View full text |Cite
|
Sign up to set email alerts
|

Dielectrophoretic capture voltage spectrum for measurement of dielectric properties and separation of cancer cells

Abstract: In this paper, a new dielectrophoresis (DEP) method based on capture voltage spectrum is proposed for measuring dielectric properties of biological cells. The capture voltage spectrum can be obtained from the balance of dielectrophoretic force and Stokes drag force acting on the cell in a microfluidic device with fluid flow and strip electrodes. The method was demonstrated with the measurement of dielectric properties of human colon cancer cells . From the capture voltage spectrum, the real part of Clausius-Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 39 publications
5
66
0
Order By: Relevance
“…The DEP response of LNCaPs measured in this work is qualitatively similar to that of cancer cells measured by other research groups [33,36,54]. Figure 3(a) shows that in the tested frequency range, the trapping potential decreased with increasing frequency, i.e., less voltage was needed to trap cells at higher frequencies.…”
Section: Dep Characterization Of Lncapssupporting
confidence: 71%
See 2 more Smart Citations
“…The DEP response of LNCaPs measured in this work is qualitatively similar to that of cancer cells measured by other research groups [33,36,54]. Figure 3(a) shows that in the tested frequency range, the trapping potential decreased with increasing frequency, i.e., less voltage was needed to trap cells at higher frequencies.…”
Section: Dep Characterization Of Lncapssupporting
confidence: 71%
“…This binary separation mechanism makes DEP an attractive tool for cell separation, as DEP requires no biochemical treatment or labeling to achieve high capture efficiency and purity. However, to date, studies using DEP methods for CTC capture have only reported high capture performance for model cancer cell lines spiked in preprocessed blood with concentrations ranging from one cancer cell per 10 4 -10 6 blood cells [33,34,36,39,40,42,44]. The commercially licensed ApoStream ™ (ApoCell) system, which uses DEP-FFF, has reported capture efficiencies in the range of 50-80% for ovarian and breast cancer cell lines spiked in peripheral blood mononuclear cells (PBMCs) with concentrations as low as one cancer cell per 10 6 blood cells, but noted that efficiency decreased after running samples through the system multiple times to increase capture purity [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since the spectra are not from the measurements of the same cells, only average electrical properties of a cell population can be obtained. [109][110][111] More details on DEP and ROT models can be found in other reviews. 9,112 The most popular ROT setup uses four electrodes connected to sine waves in phase quadrature.…”
Section: Electrorotationmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Dielectrophoresis (DEP) is a common microfluidic technique which accomplishes this using electric field gradients. [9][10][11][12][13][14][15][16][17] This has been applied to various biomedical assays, such as rare cell detection, protein separation, and enrichment of a cell population of interest. [18][19][20][21][22][23][24][25] Traditionally, the electric field gradient necessary for DEP is formed in a microchannel using two-dimensional electrodes strategically patterned on the device substrate.…”
Section: Introductionmentioning
confidence: 99%